The Concept of Tauhid According to the Rifai Order (Journal of Namibian Studies : History Politics Culture, 2022)
The concept of Tauhid is a fundamental element in the formation of Sufi teachings. A complete understanding of the concept of Tauhid leads to the truth of a teaching. Wahdat al-Wujud is one of the Sufi concepts that often becomes a subject of polemics among scholars. Wahdat al-Wujud is a doctrine that has always been a polemic among scholars causing a rejection of the Sufism teachings. This paper is related to the stance of Sufism figures among the followers of al-Rifā'iyyah Tariqa towards the Wahdat al-Wujud teachings. This paper focuses on the discussion of the general meaning of Wahdat al-Wujud and the nature of Wahdat al-Wujud according to the Sufis. In addition, this paper also focuses on the al-Rifā'iyyah Tariqa’s stance towards Wahdat al-Wujud. The methodology used to achieve the objective is qualitative methods divided into historical and textual studies. The nature of Wahdat al-Wujud is divided into two, firstly, shirk and secondly, monotheism as believed by the Sufis. However, al-Rifā'iyyah Tariqa rejects this teaching because it brings doubt to the public.